KESIAPAN GURU DALAM MENGHADAPI TANTANGAN PENDIDIKAN BERBASIS TEKNOLOGI - Dhia Fitriah; Meggie Ullyah Mirianda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Education is the gateway to a better life by fighting for the smallest things to the biggest things that every human being would normally pass. In every era there is always renewal in the education system. In the 21st century, education is required to be more advanced and easily accessible to all groups. One of them, the creation of "Industrial Revolution 4.0" in other words the era of digital-based. One of the challenges of industry 4.0, namely in the world of education is learning innovation carried out by Human Resources, in this case the teacher utilizes information technology facilities that developed rapidly in the era of revolution industry 4.0 so that it can play a role in improving the quality of learning. The challenge of education in this era is how to prepare teachers for the use of current technology and maximize the abilities that teachers have in using the latest technological equipment. Therefore, Indonesia must immediately prepare professional educators, namely educators who are able to use e-learning, because the ability of educators to use technology is one of the solutions to prepare competent millennial generations.